Crime As Entertainment or Entertainment as A Crime? - Angeline, Mia (Bina Nusantara University, 2011)
Article presents one part of pop culture is crime portrayed as entertainment in television shows. Television has the means of information and entertainment, resulting in the shift of crime shows, initially crime was portrayed in the news but due to the high popularity, it becomes part of the entertainment as well. In terms of information, the most famous of crime drama show is Crime Scene Investigation (CSI), and this show gave effect known as the CSI effect, which is people have more appreciation to scientific evidences and DNA testing in trials. On the other hand, with so many shows involving crime resulting in cultivation impact, which is accumulation and the formation of perception of reality. People who are more exposed to this crime show will form the same perception as the one depicted by television and resulted to changes in their behavior. Several proposals to reduce this negative effects are audience learning, the use of rating system and electronic key in television set.